2011
DOI: 10.1177/00333549111260s205
|View full text |Cite
|
Sign up to set email alerts
|

Improving Immunization Rates at 18 Months of Age: Implications for Individual Practices

Abstract: Practice-based interventions aimed at encouraging an 18-month well-child visit that emphasizes delivery of vaccines have the potential to substantially increase timely vaccination rates among individual practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although previous studies [1,16] have suggested that LAIV has greater VE than IIV in young children, several recent studies have not supported those findings. LAIV had low VE in 2013-2014 [3,17,18], possibly due to the heat instability of the A/H1N1 [19,20] construct, which was changed for the 2015-2016 vaccine.…”
Section: Discussionmentioning
confidence: 89%
“…Although previous studies [1,16] have suggested that LAIV has greater VE than IIV in young children, several recent studies have not supported those findings. LAIV had low VE in 2013-2014 [3,17,18], possibly due to the heat instability of the A/H1N1 [19,20] construct, which was changed for the 2015-2016 vaccine.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the variation might be due to the difference in the status of the study settings where half of the study facilities in this study are referral facilities having high client flows and creating a high workload which may reduce child screening for vaccination status. Evidence had confirmed that screening children for vaccination during any contact with health services improves immunization coverage by reducing missed opportunities for vaccinations [ 40 ]. However, the screening practice was low (58.53%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Increasing immunization rates therefore remains a perennial target for quality improvement (QI) in pediatrics. [8][9][10][11][12] Our practice began immunization improvement work in 1996 with the development of a home-grown immunization database. This database preceded the Massachusetts Immunization Information System (MIIS), launched in 2011 by the state Department of Public Health.…”
mentioning
confidence: 99%